PANDANGAN DUNIA DAN PERILAKU SEKSUAL - Pratiwi, Fita Nilam; Abraham, Juneman (Jurnal Aspirasi, 2013)
There are only a few empirical researches which connect the individual sexual behavior with the individual’s perspective in viewing the world (worldview), although speculations related to that matter have already existed in the literature. This research carried out measurement of participant’s worldview using Worldview Analysis Scale as well as participant’s sexual behavior using Garos Sexual Behavior Inventory. The participants of this research consisted of 200 people (52% male, 48% female; age average 24.23 years; standard deviation of the age 1.92 years) who were obtained by convenience sampling techniques in Jakarta, Bogor, Depok, Tangerang, Bekasi, Bandung, and Surabaya. The results show that there are correlations between communalism worldview and sexual discordance as well as tangible realism worldview and sexual discordance.